Game-based physical education: a pathway to increased student motivation and greater learning outcomes - Ezeddine, Ghaith; Souissi, Nafaa; Abaidia, Riheb; Masmoudi, Liwa; Trabelsi, Khaled; Ammar, Achraf; Jahrami, Haitham; Husain, Waqar; Tannoubi, Amayra; Kurnaz, Mert; Altınkök, Mustafa; Mrayah, Maher (Frontiers in Education, 2025)
PurposeThe aim of this study was to examine the effects of game-based learning (GBL) on students’ motivation and academic performance in physical education.MethodsOver a five-week period, a total of 51 first-year secondary school students in Tunisia (mean age = 15.0 ± 0.1 years, 50% female) were randomly assigned to an experimental group (EG) or a control group (CG). The EG received physical education instruction through a GBL approach, while the CG followed conventional, teacher-centered instruction. Learning outcomes were evaluated through Learning Time Analysis System video analysis at T0 (pre-intervention), T1 (mid-intervention), and T2 (post-intervention). Motivation was assessed pre- and post-intervention using the Situational Motivation Scale.ResultsCompared to the CG, the EG had significantly higher levels of identified regulation (5.42 ± 1.68 at T0 and 5.7 ± 0.92 at T2 for the EG vs. 4.4 ± 1.12 at T0 and 4.23 ± 1.85 at T2 for CG; p < 0.001; ηp2 = 0.26) and intrinsic motivation (5.52 ± 1.61 at T0 and 5.32 ± 1.37 at T2 for EG vs. 3.29 ± 1.34 at T0 and 4.37 ± 2.13 at T2 for CG; p < 0.001; ηp2 = 0.28). The EG also improved academic performance through improved motor engagement (50.7 ± 42.3 at T0 to 81.3 ± 20.2 at T1, to 131.4 ± 2.7 at T2; p < 0.001; ηp2 = 0.346) and reduced waiting time (82.9 ± 2.9 at T0 to 57.5 ± 3.5 at T1 and 50.3 ± 2.1 at T2; p < 0.001; ηp2 = 0.90) at both middle and post-intervention which was not always the case in the CG.ConclusionGBL significantly improved students’ motivation and engagement in physical education relative to conventional instruction. While these findings support the use of GBL as an effective pedagogical approach, the relatively small sample size suggests the need to replicate the study with larger and more diverse student populations, while also examining the long-term impact of GBL on skill retention and academic outcomes across different educational environments.